Levothyroxine malabsorption following sleeve gastrectomy - Elodie Gruneisen; Ji Wei Yang; Melissa-Rosina Pasqua (Endocrinology, Diabetes & Metabolism Case Reports)
Oral levothyroxine (LT4) is prescribed worldwide for hypothyroidism. Bariatric surgery for patients with obesity has shown a substantial, long-term weight loss and considerable improvement of obesity-related diseases. LT4 malabsorption represents a significant cause of refractory hypothyroidism, well known after malabsorptive bariatric surgery such as Roux-en-Y gastric bypass. However, few studies have shown an increase in oral LT4 needed after sleeve gastrectomy. We present a 47-year-old woman with class III obesity and a history of papillary thyroid cancer, with an excellent biochemical and structural response after total thyroidectomy and radioactive iodine. She underwent sleeve gastrectomy 3 years later and developed refractory hypothyroidism despite taking high doses of oral LT4 and ensuring compliance. The T4 absorption test confirmed gastrointestinal LT4 malabsorption. She was initiated on intramuscular LT4 and oral T3 (liothyronine) with improving symptoms and levels of thyroid-stimulating hormone.